Bandit nation : a history of outlaws and cultural struggle in Mexico, 1810-1920 - Frazer, Chris, 1959- (University of Nebraska Press, 2006)
Presents an analysis of the cultural impact that banditry had on Mexico from the time of its independence to the Mexican Revolution. This book focuses on the nature and role of foreign travel accounts, novels, and popular ballads, to analyze how and why Mexicans and Anglo-Saxon travellers used images of banditry to influence state formation.